Prevalence of Primary Angle Closure Glaucoma in the Last 20 Years: A Meta-Analysis and Systematic Review - Zhang, Nan; Wang, Jiaxing; Chen, Biyue; Li, Ying; Jiang, Bing (Frontiers in Medicine, 2021)
Purpose: This meta-analysis aims to investigate the worldwide prevalence of primary angle-closure glaucoma (PACG) and its risk factors in the last 20 years. Methods: We conducted a systematic review and meta-analysis of 37 population-based studies and 144354 subjects. PubMed, Embase, and Web of Science databases were searched for cross-sectional or cohort studies published in the last 20 years (2000-2020) that reported the prevalence of PACG. The prevalence of PACG was analyzed according to various risk factors. A random effect model was used for the meta-analysis. Results: The global pooled prevalence of PACG was 0.6% (95%CI= 0.5%~ 0.8%) for the last 20 years. The prevalence of PACG increases with age. Men are found less likely to have PACG than women (RR=0.71, 95%CI=0.53 ~ 0.93, p<0.01). Asia is found to have highest prevalence of PACG (0.7%, 95%CI= 0.6%~ 1.0%). The current estimated population with PACG is 17.14 million (95%CI=14.28~22.85) for people over 40 years old worldwide, with 12.30 million (95%CI=10.54~17.57) in Asia. It is estimated that by 2050, the global population with PACG will be 26.26 million with 18.47 million in Asia. Conclusion: PACG affects more than 17 million people worldwide, especially leading a huge burden to Asia. The prevalence of PACG varies widely across different ages, gender, and population geographic variation. Asian, female gender, and age are risk factors of PACG.